2021
DOI: 10.3390/app11073230
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Contactless Monitoring of Damage in Joints between Composite Structural Components Incorporating Sensing Elements via 3D-Printing

Abstract: A vibration-testing framework for detecting and identifying failing joints between composite structural members without dedicated equipment (accelerometers, amplifiers) or time-consuming system modeling methods is introduced. The sensing element is a 2826MB Metglas® magnetoelastic strip embedded in one of the members during its 3D-printing (layer-by-layer) fabrication process in fused deposition modeling mode. External dynamic loading of the structure causes changes to the strip’s magnetization, thus inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Comparison of the two series of recorded voltage signals led to two conclusions. First, the time histories of both voltage series were almost identical, as expected for passive setups [18]. Second, the spectral characteristics of the voltage with the beam under excitation were different than those from the voltage recorded with the beam at rest.…”
Section: Methodology For the Evaluation Of The Sensing Characteristic...mentioning
confidence: 55%
See 4 more Smart Citations
“…Comparison of the two series of recorded voltage signals led to two conclusions. First, the time histories of both voltage series were almost identical, as expected for passive setups [18]. Second, the spectral characteristics of the voltage with the beam under excitation were different than those from the voltage recorded with the beam at rest.…”
Section: Methodology For the Evaluation Of The Sensing Characteristic...mentioning
confidence: 55%
“…Using a passive setup, fault diagnosis was achieved in polymer slabs with magnetoelastic ribbons integrated with 3D printing during slab manufacturing [17]. Fault diagnosis was also achieved for structures composed by bolting together such slabs, and specifically, for indicating loose connections between structural members [18]. Interestingly, this study demonstrated that although only one slab with integrated magnetoelastic material was used in the structure, more than one loose connection could be detected.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations